1994
DOI: 10.1901/jaba.1994.27-413
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis Methodology: Some Closing Comments

Abstract: Functional analysis methodologies have emerged as powerful tools in research on the assessment and treatment of severe behavior disorders. Although the defining feature of these approaches is the systematic identification of environmental determinants of behavior, research methodology has varied widely with respect to the arrangements used to demonstrate experimental control as well as the types of variables subject to analysis. This commentary summarizes methodological and conceptual issues that have been rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 14 publications
1
39
0
1
Order By: Relevance
“…Some investigators have suggested that formal descriptive assessments should be routinely conducted prior to experimental analyses (e.g., . However, others have argued that the utility of combining descriptive assessments and experimental analyses has not been clearly established, in part because interviews and rating scales tend to be unreliable and the results of direct methods do not always correspond to those of experimental analyses (Iwata, 1994;Lerman & Iwata, 1993;Sturmey, 1994). Therefore, we have attempted to use descriptive information conservatively, primarily when the results of an experimental analysis are inconclusive and responding was not maintained at consistent levels in any of the conditions.…”
mentioning
confidence: 99%
“…Some investigators have suggested that formal descriptive assessments should be routinely conducted prior to experimental analyses (e.g., . However, others have argued that the utility of combining descriptive assessments and experimental analyses has not been clearly established, in part because interviews and rating scales tend to be unreliable and the results of direct methods do not always correspond to those of experimental analyses (Iwata, 1994;Lerman & Iwata, 1993;Sturmey, 1994). Therefore, we have attempted to use descriptive information conservatively, primarily when the results of an experimental analysis are inconclusive and responding was not maintained at consistent levels in any of the conditions.…”
mentioning
confidence: 99%
“…Under these circumstances, help is reinforcing because (like Michael's screwdriver) it changes the task into an easier one that does not establish motivation to escape. Help, of course, is one kind of attention so that, if such a transitive relation already exists, problem behavior in the context of demands may be attention rather than escape maintained (Iwata, 1994;Repp & Karsh, 1994;Rortvedt & Miltenberger, 1994).…”
Section: Functional Communication Training (Fct)mentioning
confidence: 99%
“…This study examined the results of the extended duration functional analysis procedures of Kahng, Abt, and Schonbachler (2001) with six children admitted to an inpatient hospital for the treatment of severe problem behavior. Results of initial functional analyses (Iwata, Dorsey, Slifer, Bauman, & Richman, 1982/1994 were inconclusive for all children because of low levels of responding. The altered functional analyses, which changed multiple variables including the duration of the functional analysis (i.e., 6 or 7 hrs), yielded clear behavioral functions for all six participants.…”
mentioning
confidence: 95%
“…he development of a functional analysis of problem behavior (Iwata, Dorsey, Slifer, Bauman, & Richman, 1982/1994) transformed the treatment process for self-injurious behavior (SIB) and other problem behaviors by allowing clinicians and researchers to systematically identify the determinants of problem behavior. This functional analysis technology minimized the trial and error approach to treatment selection by allowing the clinician to predict which interventions were more likely to be effective (i.e., those directly designed to address the function of the problem behavior; Iwata, Pace, Cowdery, & Miltenberger, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation